Pesantren and Theory of Social Change in Southeast Asia - Munzier Suparta (Review of Islam in Southeast Asia, 2018)
Pesantrens or islamic boarding schools have become a common model of religious education in some countries in Southeast Asia, especially in Indonesia, Malaysia, Southern Thailand, and Southern Philippines. Muslim scholars (Ulemas) from Southeast Asian countries learned and shared each other on Islamic studies. Up to 1980s, students from Malaysia, Southern Thailand and Singapore studied Islamic studies at Indonesian Pesantrens. This model of pesantren teaching affected to the regional perspectives of practicing Islam accomodating local tranditions. Some Patani Ulema of Southern Thailand delivered the tradition of recitation of Islamic studies books with Javanese (pegon) letters in pesantren and madrasah. Furthermore, the scholars constructed Southeast Asian Muslims developing moderate and peaceful Islam, and created Muslim leaders in the region. They become cultural brokers or mediators in social, political and economic development. This article is based on fieldworks in some pesantrens in Indonesia and Southeast Asia.